2011
DOI: 10.1111/j.1525-142x.2011.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological “primary homology” and expression of AG -subfamily MADS-box genes in pines, podocarps, and yews

Abstract: The morphological variation among reproductive organs of extant gymnosperms is remarkable, especially among conifers. Several hypotheses concerning morphological homology between various conifer reproductive organs have been put forward, in particular in relation to the pine ovuliferous scale. Here, we use the expression patterns of orthologs of the ABC-model MADS-box gene AGAMOUS (AG) for testing morphological homology hypotheses related to organs of the conifer female cone. To this end, we first developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
(95 reference statements)
2
24
0
1
Order By: Relevance
“…Specifically, our data indicate that CjMADS4, TdMADS3, and JcMADS2 are the orthologs in each respective species both to each other and to DAL2 and SAG1 in Picea abies and Picea mariana, respectively. Our data further indicate that these genes are orthologous to PodAG and TgAG (Englund et al 2011), in the conifer families Podocarpaceae and Taxaceae, respectively. We cannot exclude the possibility that in one or more of these conifer species there are AG subfamily genes paralogous to the gene presented here present in the genome.…”
Section: Dal2/sag1 Orthologs In Cupressaceae and Taxodiaceaesupporting
confidence: 69%
See 2 more Smart Citations
“…Specifically, our data indicate that CjMADS4, TdMADS3, and JcMADS2 are the orthologs in each respective species both to each other and to DAL2 and SAG1 in Picea abies and Picea mariana, respectively. Our data further indicate that these genes are orthologous to PodAG and TgAG (Englund et al 2011), in the conifer families Podocarpaceae and Taxaceae, respectively. We cannot exclude the possibility that in one or more of these conifer species there are AG subfamily genes paralogous to the gene presented here present in the genome.…”
Section: Dal2/sag1 Orthologs In Cupressaceae and Taxodiaceaesupporting
confidence: 69%
“…TdMADS3, JcMADS2, and CjMADS4 all belong to the conifer section of the AG clade, together with the Picea protein DAL2. Sequences for the conifer genes PodAG ( Podocarpus reichei ) and TgAG ( Taxus globosa ) are characterized in more detail in Englund et al (2011). For accession numbers of all proteins included in the analysis, see supporting information Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that DAL2 was expressed throughout the nucellus and the outer cell layers of the integument (Fig. e,i,k; Englund et al ., ), whereas DAL14 expression was detected throughout the integument, but not in the nucellus (Fig. f,j,l).…”
Section: Resultsmentioning
confidence: 97%
“…Transcription factors of the MADS-domain family play key roles in both processes, in addition to LEAFY (LFY), which acts as an initiator of the floral-organ identity MADS-box genes. The gymnosperm homologues to the MADS-box C-class genes, in angiosperms specifying carpel identity and, together with the B genes, stamen development, are all expressed in ovule-carrying and pollen-producing organs, whereas B-class homologues appear to be specific to the pollen-producing organs (Tandre et al, 1995(Tandre et al, , 1998Rutledge et al, 1998;Sundstr€ om et al, 1999;Winter et al, 1999;Sundstr€ om & Engstr€ om, 2002;Carlsbecker et al, 2003Carlsbecker et al, , 2004Jager et al, 2003;Zhang et al, 2004;V azquez-Lobo et al, 2007;Englund et al, 2011;Groth et al, 2011;Lovisetto et al, 2012). Hence, a substantial conservation of reproductive development control is apparent and implies that C-class homologues specify reproductive identity and B-class homologues distinguish male from female identity in all seed plant groups.…”
Section: Introductionmentioning
confidence: 99%